Numerical Calculation of Three Phase Flow (Gas – Solid – Liquid) of Thermal Spray Process - Hafiz Bin Mohd Noh, Mohd; SAWADA, Naoki; MORI, Koichi (International Journal of Engineering and Technology, 2018)
A new coupling method between the FVM (Finite Volume Method) - solution for compressible gas flows and the MPS (Moving Particle Semi-implicit) - solution for droplet deformation have been developed. This simulation of thermal spray processes covered from the acceleration until droplet substrate solidification. At the temperature of 300K, the trend of flatness result is proportional to Re0.26, which agreed well with the experimental result. The adhesive efficiency and aspect ratio are also improved under FVM + MPS calculation as compared with the calculation of MPS only.Â Â Â